a) ) (+6) + (-1) + (-5) + (-3) =
b) (-10) - (-2) - (+4) - (-1) =
c) (-4) - (+2) - (-1) + (-5) =
d) (+ 3) - (-2) + (-9) + (-5) =
Me ajuda ae se fazer graça denuncio!!
Soluções para a tarefa
Respondido por
0
Resposta:
a)(-3)
b)(+13)
c)(+12)
d)(+19)
Explicação passo-a-passo:
a)(+6)+(-1)+(-5)+(-3)=(-5)+(+8)=(-3)
b)(-10)-(-2)-(+4)-(-1)=(-8)-(+5)=(+13)
c)(-4)-(+2)-(-1)+(-5)=(+6)-(-6)=(+12)
d)(+3)-(-2)+(-9)+(-5)=(+5)+(+14)=(+19)
Perguntas interessantes
Inglês,
8 meses atrás
Psicologia,
8 meses atrás
Saúde,
8 meses atrás
Matemática,
11 meses atrás
Artes,
11 meses atrás
Inglês,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás